FORTIFIKASI TEPUNG WORTEL DALAM PEMBUATAN BUBUR INSTAN UNTUK PENINGKATAN PROVITAMIN A - Agus Slamet (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Malnutrition, particularly vitamin A is still a problem in Indonesia. Vitamin A plays an important role in sustaining life. The main role of vitamin A in the body is as a regulator of cell structure metabolism. Carrots are a potential source of vitamins. Vitamin found in carrots at 12,000 SI. To overcome the problem of vitamin A deficiency by using the carrot mixture of several kinds of wheat flour and make practical in food processing, easy to prepare and tune. Instant Porridge is a simple fast food in processing, presentation and the like starting from toddler age up to the parents. Variation of treatment used are various types of flour and the number of additional carrots flour. A variety of wheat used was: flour carrot, arrowroot flour: flour carrot and cassava flour: flour carrot. Variation number 100:0, 90:10, 80:20 and 70:30. Analysis performed: physical properties include: water absorption capacity, color, rehydration rate. Chemical properties include: water content, protein, ash, starch and β-carotene. This product is also tested with the level of his favorite method of hedonic test. The results of this study concluded that the preferred instant porridge made with flour carrot mixture of flour and cassava flour: carrot flour with variations in 70:30. Instant porridge has a β-carotene content of 3891.78 g / g